Malta : 2015 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This 2015 Article IV Consultation highlights that Malta's economy is growing strongly. Real GDP growth has been one of the highest in the euro area since the beginning of the crisis, supported by vibrant domestic demand, large infrastructure projects, and a stable banking sector. Unemployment is at historical lows, and labor participation is increasing. The current account remains in surplus, and the external position is broadly in line with fundamentals. Growth is expected to remain solid in 2016-17, driven initially by domestic demand and later by a gradual recovery of external demand. Inflation is projected to pick up gradually owing to the positive output gap and higher imported inflation on account of the weaker exchange rate.